PANCASILA EDUCATION TO IMPROVE THE MORALE OF THE MILLENNIAL GENERATION - Maliah, Iin; Pandin, Moses Glorino Rumambo (Ganesha Civic Education Journal, 2024)
Indonesia as a country based on Pancasila requires every university to provide Pancasila courses to its students for at least one semester. This article was created in line with the hope of saving the morals of the millennial generation through Pancasila courses. This study has questions related to moral damage, namely the impact of moral damage on the millennial generation. Who conducted this research to answer the question about the impact of moral damage on the millennial generation? This research was conducted using a literature study method that summarized ten articles published from 2019 to 2021 from two online databases: Scopus and Google Scholar. The eligibility of this research institution is seen from the title, abstract, methodology, results, and discussion. The results presented in narrative form show that the morals of the millennial generation have been damaged so far. This moral decline can be overcome by continuing to provide Pancasila courses in universities. Thus, the character of the millennial generation can be strengthened with Pancasila moral education. The implication of this research is that it can be a strong empirical foundation for revising and developing a Pancasila Education curriculum that is more relevant, interesting, and effective for the millennial generation. The curriculum can be designed to be more contextual to the challenges of the times and use learning methods that suit the learning styles of this generation.